Assessing and enhancing migration of human myogenic progenitors using directed iPS cell differentiation and advanced tissue modelling - SungWoo Choi; Giulia Ferrari; Louise A Moyle; Kirsty Mackinlay; Naira Naouar; Salma Jalal; Sara Benedetti; Christine Wells; Francesco Muntoni; Francesco Saverio Tedesco (EMBO Molecular Medicine)
Abstract Muscle satellite stem cells (MuSCs) are responsible for skeletal muscle growth and regeneration. Despite their differentiation potential, human MuSCs have limited in vitro expansion and in vivo migration capacity, limiting their use in cell therapies for diseases affecting multiple skeletal muscles. Several protocols have been developed to derive MuSC‐like progenitors from human induced pluripotent stem (iPS) cells (hiPSCs) to establish a source of myogenic cells with controllable proliferation and differentiation. However, current hiPSC myogenic derivatives also suffer from limitations of cell migration, ultimately delaying their clinical translation. Here we use a multi‐disciplinary approach including bioinformatics and tissue engineering to show that DLL4 and PDGF‐BB improve migration of hiPSC‐derived myogenic progenitors. Transcriptomic analyses demonstrate that this property is conserved across species and multiple hiPSC lines, consistent with results from single cell motility profiling. Treated cells showed enhanced trans‐endothelial migration in transwell assays. Finally, increased motility was detected in a novel humanised assay to study cell migration using 3D artificial muscles, harnessing advanced tissue modelling to move hiPSCs closer to future muscle gene and cell therapies.